Questioning the validity of food addiction: a critical review - Oliveira, Jônatas; Bestetti, Giulia Cazetta; Stelmo, Isis De Carvalho; Antunes, Larissa; Vilella, Priscylla Rodrigues (Frontiers in Behavioral Neuroscience, 2025)
Food cravings (FC) are closely associated with behaviors such as loss of control, binge eating, and emotional eating. Although FC is among the symptoms proposed for food addiction (FA), we argue that the distress associated with eating, managing cravings, and experiencing loss of control may not, in itself, constitute a framework consistent with addiction or addiction-like eating. Grouping these concepts under the FA label may contribute to conceptual confusion, potentially leading to diagnostic inaccuracies. This integrative review aimed to explore the concepts of FA and FC, as well as their interrelations, through methodologies such as self-report questionnaires and visual analog scales. A systematic search without time restrictions yielded 37 original studies for qualitative analysis. The selected investigations examined FA and FC as primary outcomes and were categorized into five thematic sections: (1) genetic factors, (2) neurobiology, (3) behavioral factors, (4) emotional factors, and (5) food cues. The findings indicate that cravings play a mediating role in disordered eating patterns and are associated with excessive consumption or impaired control in individuals exhibiting symptoms attributed to FA. This review addresses three key issues: (i) theoretical and psychometric challenges in the conceptualization of FA, (ii) redundancies among FC, eating-related distress, and self-reported loss of control, and (iii) whether FA is primarily a matter of semantics. Phrases related to constructs of substance use disorders correlate with constructs that are neuropsychopharmacological influenced, and they impose new constructs upon previously established eating behavior patterns, along with their already known neural and neuropsychological correlates (such as emotional eating, dietary restraint, binge eating, and craving). The concept of FA, along with its scale and the new diagnostic questionnaire, also integrates cultural perceptions of food with established psychological constructs, drawing on previously recognized phenomena. Investigating the continuum encompassing (i) cravings, (ii) disordered eating attitudes, and (iii) body image–related distress presents a significant challenge, particularly when researchers overlook the underlying human narratives that define this multifaceted phenomenon. Without a clear theoretical and epistemological framework, the boundaries of FA risk becoming overly broad, diminishing its utility as a diagnostic tool or basis for interventions. The challenges in establishing a consistent and precise definition underscore the need for further research to ensure the concept represents a distinct and scientifically valid phenomenon rather than a generalized reflection of eating-related constructs.